Postgraduate study as an education program (round table discussion) - Editorial Article (Moscow Polytechnic University, 2022)
On March 20, 2013 a round table discussion on the theme "Postgraduate study as an education program" was held in the framework of the Third IGIP international regional conference and the annual MADI methodological seminar "Innovative pedagogical technologies in engineering education". The organizers of the discussion were The State Technical University - MADI and the journal "Higher Education in Russia". The participants took up the topical questions concerning thepostgraduate study in the context of forthcoming organizational reforms in higher education.